Comparison of the features of the formation of joints of aluminum alloy 7075 (Al-Zn-Mg-Cu) by laser, microplasma, and laser-microplasma welding - Korzhyk, Volodymyr; Khaskin, Vladyslav; Grynyuk, Andrii; Peleshenko, Sviatoslav; Kvasnytskyi, Viktor; Fialko, Nataliia; Berdnikova, Olena; Illiashenko, Yevhenii; Shcheretskiy, Volodymyr; Yao, Yuhui (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into features of the formation of structures of permanent butt joints of plates with a thickness of 1.5 mm made from the high-strength aluminum alloy 7075 of the Al-Zn-Mg-Cu system. Welding by melting these joints was performed using three techniques: laser, microplasma, and hybrid laser-microplasma. To implement the latter two, a compressed arc on a multipolar asymmetric current was used. The purpose of the research was to establish the tendency to the formation of characteristic defects and the possibility of their elimination. It has been determined that during laser welding a small ( 5 %) volumetric fraction of defects in the form of pores is formed, residual welding deformations are minimized. There is a decrease in the hardness of the melted metal by 15 % with a simultaneous increase in the hardness of the heat-affected zone (HAZ) by 8...12 % relative to the base metal. In the melted metal, cavities up to 100 μm in size are formed, which are the center of the origin of hot cracks with a length of 25‒30 μm. There are oxide inclusions in the root part of the seam. With microplasma welding, the volume fraction of defects of the melted metal in the form of pores with a size of 10...105 μm increases (up to 25 %). The hardness of the melted metal is reduced by 30 % with the hardness of the HAZ metal close to the base metal. In laser-microplasma welding, the volumetric fraction of defects of the melted metal in the form of pores with a size of 15...25 μm is reduced to 5 %. The hardness of the melted metal is reduced by 15...20 % with the hardness of the HAZ metal close to the base metal. In the lower part of the melted metal, cavities of 100 μm are formed. No microcracks were found in the seam metal. Analysis of the research results showed the advantage of the laser-microplasma technique. This method reduces the use of laser energy by 40...50 %, the lifetime of the welding pool (0.03...0.05 s) approaches laser welding, it eliminates the danger of burnout of alloying elements.